A comparative study on vibhitakaadi ghrita tarpana and putapaka in the management of vataja timira with special reference to astigmatism - Shwetha R; S M Pasha (International Journal of Pharmacy and Analytical Research, 2022)
Background Astigmatism is a refractive error where in the refraction varies in different meridians, resulting in blurriness & distorted of vision. The increase in the incidence of astigmatism along with other refractive errors is due to the present life style, where in there is excessive use of computers, television and junk food1. Avyakta darshana, vyavidha darshana is the symptom mentioned in vataja timira2, which is seen in astigmatism, where in the patient experiences blurrness and distorted of vision. Our acharyas have mentioned number of kriyakalpas, yogas and chakshushya regime for curing Timira. Tarpana is one such kriya kalpa, which is non-invasive and cost effective, Vibhitakaadi ghrita is described as a potent yoga, which cures many netra rogas including timira. So in present study an attempt is made to evaluate the effect of Vibhitakaadi ghrita tarpana and putapaka in vataja timira. The assessment of the result was done based on the subjective and objective parameters. Results It is statistically proved that overall effect of Vibhitakaadi ghrita tarpana and Putapaka (group B) showed better results in comparison to tarpana with Vibhitakaadi ghrita (group A).